The Bridging Inequality in Environmental Governance: A Case Study of Waste Management in Kupang City, Indonesia - Muhammad Rifki Rosman; Rahman Mulyawan; Neneng Yani Yuningsih (Dealings Foundation Institute, 2026)
Waste management in Kupang City continues to face complex challenges that are not only technical but also closely related to issues of equity in environmental governance. This study aims to examine how the principle of equity is implemented in waste management governance in Kupang City using the environmental governance framework proposed by Bennett and Satterfield. A qualitative case study approach was employed to explore the experiences and perspectives of multiple stakeholders, including local government officials, environmental communities, private sector actors, and affected residents. Data were collected through interviews, observations, and document analysis and were analyzed thematically. The findings reveal that the Kupang City Government has demonstrated an initial commitment to inclusive waste governance by involving diverse stakeholders, including vulnerable groups, in waste management initiatives and community surveys. However, participation remains largely concentrated at the implementation stage and is not yet fully integrated into policy planning and evaluation processes. The study also identifies significant inequalities in the distribution of waste management services, particularly in the availability of waste collection facilities and transportation services in suburban areas. Furthermore, communities living near the Alak landfill continue to bear disproportionate environmental and health risks without adequate protection mechanisms. This study contributes to the environmental governance literature by providing empirical evidence on how equity principles operate in urban waste management in developing cities. Strengthening institutional capacity, expanding participatory mechanisms, and improving the protection of vulnerable groups are essential to achieving more inclusive and sustainable waste governance in Kupang City, Indonesia.